Ginger Cultivation and Its Antimicrobial and Pharmacological Potentials - Wang, Haiping (IntechOpen, 2020)
Ginger is well known as a spice and flavor. It has been a traditional medical plant in many cultures for thousands of years. To uncover the miraculous plant, this book not only gives you the plant's origins, where the plant is grown now, but also provides current studies on its utilization, cultivation, breeding, and therapeutic benefits.